Detection and estimation of the spin of a ping pong ball - Qing, Yuanyuan (2016)
With the fast development of modern technology, people start to apply technological methods to analyze various kinds of sport games, in order to better understand the sport and also to improve the athlete performance in a smart way. For many ball games, the spinning or rotation of the ball is of vital importance, especially for the game of Ping-Pong. Ping-Pong, also known as table tennis, is one popular sport in the world. As we know, Ping-Pong is a game of spin, as different types of ball spin will require the athlete to respond differently. ITTF (International Table Tennis Federation) together with ISR (Institute for Sports Research) proposed the idea of making use of radar to detect the Ping-Pong ball spinning. Therefore, in this project, Doppler radar sensing is used for the tracking of Ping-Pong ball to detect and estimate the spinning of the ball. The experiment results showed the possibility of accurate detection of spinning speed for Ping-Pong in simple situations. However, due to hardware limitations, the detection in relatively complex cases will be quite difficult. Therefore, some theoretically possible ways of detection 3D spin of Ping-Pong are also discussed.